The Financial Literacy and M-Payment Ease of Use on Impulsive Buying of Virtual Goods - Rosyada, Amryna; Putikadea, Insyirah (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2026)
This study aims to examine the effect of financial literacy and the perceived ease of use of mobile payments (m-payment) on the impulsive buying behavior of virtual goods among active Roblox players. The rapid growth of the digital gaming industry necessitates a deeper understanding of contemporary consumer behavior. A quantitative descriptive method was employed, utilizing purposive sampling to collect data from 100 active Roblox players aged 18–30 within an online community. Data were analyzed using multiple linear regression. The findings reveal that financial literacy has a significant negative effect on impulsive buying behavior, acting as a crucial control mechanism against unplanned purchases. Conversely, the ease of use of m-payment has a significant positive effect, serving as a trigger for impulsive buying due to its convenience. Collectively, both variables account for 21.9% of the variance in impulsive buying behavior. This research extends the Theory of Planned Behavior in the context of virtual economies, highlighting the dual role of financial knowledge and technological convenience in shaping digital consumption.